Usefulness of bedside ultrasound for lumbar puncture: an analysis of evidence-based diagnostic performance - Lozada Martinez, Iván David (2022)
Advances in biomedical technology have increased the success rate of medical procedures due to improvements in safety and efficacy. During the assessment of patients with acute neurological disorder who require a lumbar puncture, some conditions may hinder its performance, such as infection at the puncture site or bone abnormalities that may cause spinal cord injury. Bedside ultrasound is a good alternative to assist in the performance of a puncture, due to its ability to examine structures that cannot be assessed by physical examination. In primary health care centers, where there may be obstacles that prevent access to expensive imaging tools, ultrasound is a cost-effective option in the approach to urgent pathologies. In view of the foregoing, this paper aims to review important recent evidence-based concepts related to the use of ultrasound for the performance of a lumbar puncture.